Anther Morphological Development and Stage Determination in Triticum aestivum - Browne, Richard G.; Iacuone, Sylvana; Li, Song F.; Dolferus, Rudy; Parish, Roger W. (Frontiers in Plant Science, 2018)
Anther development progresses through 15 distinct developmental stages in wheat, and accurate determination of anther developmental stages is essential in anther and pollen studies. A detailed outline of the development of the wheat anther through its entire developmental program, including the 15 distinct morphological stages, is presented. In bread wheat (Triticum aestivum), anther developmental stages were correlated with five measurements, namely auricle distance, spike length, spikelet length, anther length and anther width. Spike length and auricle distance were shown to be suitable for rapid anther staging within cultivars. Anther length is an accurate measurement in determining anther stages and may be applicable for use between cultivars. Tapetal Programmed Cell Death (PCD) in wheat begins between late tetrad stage (stage 8) and the early young microspore stage (stage 9) of anther development. Tapetal PCD continues until the vacuolate pollen stage (stage 11), at which point the tapetum fully degrades. The timing of tapetal PCD initiation is slightly delayed compared to that in rice, but is two stages earlier than in the model dicot Arabidopsis. The MYB80 gene, which encodes a transcription factor regulating the timing of tapetal PCD, reaches its peak expression at the onset of tapetal PCD in wheat.